Rapid review on the use of new age induced breeding agent ‘LHRHa’ in Indian finfish seed production sector - Roy, Koushik (Journal of Fisheries, 2016)
A focused review on the use of LHRHa in induced breeding of fishes in India was made. Use of LHRHa is mainly restricted to high value brackish water and marine fish species whose market value generally exceeds INR 300-400/kg (USD 4.5-6/kg). Published information on use of LHRHa in induced breeding of fishes in India could document only twelve species out of which nine were brackishwater or marine fish. Besides length and weight, the egg diameter of female fishes (>0.45–0.7 mm) is an important criterion for treating the fishes with LHRHa. LHRHa is either used alone or in combination with HCG (most popular), PGE, 17α-MT and Pimozide. Dosage of 20-70 µg/kg body weight for females and 10-40 µg/kg body weight for males with a latency period of 24-36 hours is most common in India. Experiments with LHRHa are being carried out mainly by ICAR-CIBA, Chennai (dominant) and ICAR-CMFRI, Kochi. Standardization and optimization of LHRHa dosage has been attained in Asian Seabass (Lates calcarifer), Cobia (Rachycentron canadum), Grey mullet (Mugil cephalus) and Spotted scat (Scatophagus argus) while in Grouper (Epinephelus tauvina), Moonfish (Monodactylus argenteus), Milk fish (Chanos chanos), Crescent Bass (Terapon jarbua) and Silver Pompano (Trachinotus blochii), it is under progress.